A sustainability management model for local government: An explanatory study - Fabio De Matteis; Elio Borgonovi (Administrative Sciences, 2021)
Although the scientific debate in the field of business economics is rich in contributions to the subject of sustainability, they mainly focus on a specific aspect represented by sustainability reporting. Consistent with this bibliographic evidence, the aim of this study was to investigate a sustainability management model in local authorities, which, by examining the dimensions of sustainability, goes beyond the focus of reporting highlighted in the literature to consider the entire sustainability cycle (from planning to measurement). To this end, the methodology of the single case study with multiple units of analysis is used, examining the case of an Italian local authority that has experimented with the sustainability management model described in this paper. The analysis of the case leads to some concluding remarks on the strengths and weaknesses of the model, contributing to the scientific debate on sustainability management and providing useful indications for public managers and political decision-makers.
Keywords: 350; local government; sustainability management